The Role of the Islamic Boarding School Environment in the Internalisation of Akhlāqul karīmah Values: A Study at the Ibnul Qoyyim Putri Islamic Boarding School through the Book Akhlāq Lil Banāt - Azzizah, Azzahra Nurul; Mujahid (Kalijaga Journal of Islamic Religious Education, 2025)
The phenomenon of moral degradation among youth, particularly female students, has become a serious challenge for Islamic education. This condition demands the strengthening of moral education through classical texts and the pesantren environment. This study aims to analyze the values of akhlāqul karīmah in the book Akhlāq Lil Banāt, their internalization in students’ daily lives, and the role of Ibnul Qoyyim Islamic Boarding School in supporting the internalization of these values. A descriptive qualitative approach was employed using interviews, observations, and documentation, involving the kitab instructor, students, and the caretaking division. The findings reveal that akhlāqul karīmah values include morality towards Allah, parents, teachers, siblings, peers, and society. These values are practiced through worship, discipline, manners of speech, and social interaction. The pesantren environment, both physical aspects (dormitory, mosque, classrooms, library) and non-physical aspects (boarding culture, caretaking, teacher role models, and religious atmosphere), plays a crucial role in shaping students’ morality. Thus, the internalization of moral values depends not only on kitab learning but also on a supportive pesantren environment.